Changes in the Distribution of Pectin in Root Border Cells Under Aluminum Stress - Nagayama, Teruki; Nakamura, Atsuko; Yamaji, Naoki; Satoh, Shinobu; Furukawa, Jun; Iwai, Hiroaki (Frontiers in Plant Science, 2019)
Root border cells (RBCs) surround the root apices in most plant species and are involved in the production of root exudates. We tested the relationship between pectin content in root tips and aluminum (Al) tolerance by comparing these parameters in wild-type (WT) and sensitive-to-Al-rhizotoxicity (STAR1) mutant rice plants. Staining for demethylesterified pectin decreased after Al treatment in the WT. A high level of pectin was observed in RBCs of the root tips. The level of total pectin was increased by about 50% compared with the control. In the Al-sensitive STAR1 mutant, Al treatment decreased root elongation and pectin content, especially in RBCs. In addition, almost no Al accumulation was observed in the control, whereas more Al was accumulated in the RBCs of STAR1 roots. These results show that the amount of pectin influences Al tolerance; that Al accumulation in rice roots is reduced by the distribution of pectin in root-tip RBCs; and that these reactions occur in the field around the RBCs, including the surrounding mucilage. Al accumulation in rice roots is reduced by the distribution of pectin in root tips, and pectin in the root cell walls contributes to the acquisition of Al tolerance in rice by regulating its distribution. The release of Al-binding mucilage by RBCs could play a role in protecting root tips from Al-induced cellular damage.